How the eurobarometer blurs the Line between research and propaganda - Martin Höpner; Bojan Jurczyk (Max Planck Institute for the Study of Societies, 2015)
This paper reviews Eurobarometer surveys from 1995 to 2010 and shows how Eurobarometer selects and frames questions in ways that systematically produce "integrationist" outcomes. The violations of the rules of good public opinion research concern incomprehensible, hypothetical, and knowledge-inadequate questions, unbalanced response options, insinuation and leading questions, context effects, and the strategic removal of questions that led to critical responses in previous Eurobarometer waves. It is highly unlikely that the violations happen unintentionally. Eurobarometer therefore blurs the line between research and propaganda. – – Dieses Paper unterzieht die zwischen 1995 und 2010 durchgeführten Eurobarometer-Umfragen einer kritischen Überprüfung und weist nach, wie Fragen so ausgewählt und formuliert werden, dass sie zu "integrationistischen" Ergebnissen führen. Die Verletzungen der Regeln guter Umfrageforschung betreffen die Nutzung von überkomplizierten, hypothetischen und wissensinadäquaten Fragen, die Vorgabe einseitig gepolter Antwortkategorien, Suggestivfragen, Kontexteffekte sowie die strategische Entfernung von Fragen, die in früheren Befragungswellen zu unerwünschten Ergebnissen führten. Es ist sehr unwahrscheinlich, dass diese Regelverletzungen unintendiert geschehen. Das Eurobarometer verwischt daher die Grenze zwischen Forschung und Propaganda.
Keywords: 300